Low‐dose anti‐CD3 antibody induces remission of active autoimmune hepatitis in xenoimmunized mice. (11th March 2014) - Marceau, Gabriel; Yang, Roland; Lapierre, Pascal; Béland, Kathie; Alvarez, Fernando
Abstract Background Some patients with autoimmune hepatitis (AIH), despite appropriate treatment, progress towards cirrhosis and liver failure, requiring transplantation. New biological agents targeting immune cell subtypes have been developed, with better specificity and longer‐lasting effects than conventional wide‐spectrum immunosuppressive drugs. Aims The goal of this study was to evaluate the effectiveness of low dose of αCD3 targeting therapy in a model of type 2 AIH. Methods This experimental model is based on xenoimmunization of C57BL/6 mice with DNA coding for human liver autoantigens. Mice with AIH were treated with five daily injections of low dose of αCD3 monoclonal antibody, before disease onset (5.5 months post‐xenoimmunization) or during AIH (7 months post‐xenoimmunization). Along with serum aminotransferases, autoantibody levels and end‐point liver histology, spleen and liver‐infiltrating lymphocytes were phenotyped by flow cytometry and immune response measured by lymphoproliferative assays. Results Before onset of AIH, treatment prevented the development of liver inflammation and tissue injury. During active AIH, low dose of αCD3 antibody therapy resulted in a resorption of liver inflammatory infiltrates, normalization of serum aminotransferas levels, reduced autoantibody titres, increased regulatory T cells and lowered proliferation of autoreactive liver lymphocytes. Conclusions We report that low dose αCD3 antibody administration is an effective treatment for AIH in an experimental model of type 2 AIH. These data suggest that αCD3 antibody therapy could be tested in clinical trials as a rescue therapy for patients with uncontrolled AIH.